Organizational Culture to improve Public Services in Luragung District - Firdausijah, R. Taqwaty (Jurnal Sosial Sains dan Komunikasi, 2023)
Good public services are an important element in efforts to realize sustainable development and improve the quality of life of the community. Organizational culture has a crucial role in shaping attitudes and behavior in providing effective and efficient public services. This study aims to analyze the role of organizational culture in improving public services in Luragung District, Kuningan Regency, West Java. This research uses a qualitative approach with descriptive methods. The results of the study show that organizational culture to improve public services in Luragung District can be carried out with good interaction and communication, commitment to working time, and a culture of complementing public service facilities and infrastructure. This research also found several challenges that needed to be faced, such as low employee competence and capacity, lack of organizational skills, lack of awareness and commitment to public services, and lack of adaptability to change.